Femoral Artery Dopplerfluxometry of Adult Healthy Dogs (Canis lupus familiaris) - Charas dos Santos, Ivan Felismino [UNESP]; Inamassu, Leticia Rocha [UNESP]; Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Castro Martins, David Jose de [UNESP]; Ferro, Barbara Sardela [UNESP]; Silva, Bruna Martins da [UNESP]; Ferreira, Gustavo Manea [UNESP]; Branco, Marina Paiva [UNESP]; Siqueira Silva Junior, Jose Ivaldo de [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: In Veterinary Medicine, there are several methods for early and accurate assessment of blood flow dynamics. The Dopplerfluxometry can access the peak systolic velocity, mean velocity and end diastolic velocity, including Resistive Index and Pulsatility Index. Normal values of Dopplerfluxometry in healthy dogs allow the identification of vascular abnormalities and authors' knowledge there are no reference regarding the values of Dopplerfluxometry of the femoral artery in healthy dogs. The aim of the study was to assess the femoral Dopplerfluxometry of adult healthy dogs by Resistive Index, Pulsatility Index, systolic and diastolic velocities, and femoral artery diameter. Materials, Methods & Results: Eighteen healthy intact beagle dogs, male and female, aging from 2 to 4 years old (mean +/- SD: mean 3 +/- 0.8 years), weighing from 10.1-17.9 kg [22.3-39.5 Ib] [mean +/- SD: 14.3 +/- 2.7 kg (31.5 +/- 5.96 Ib)] were used. The dogs underwent to physical examination, complete blood cell count, serum biochemistry examination urinalysis, and radiographs examination, muscular and cardiac evaluation. Females had to be in anestrous. All dogs were submitted to right femoral artery Dopplerfluxometry. The dogs were positioned in dorsal recumbency by one person without any chemical restraint. A high definition ultrasound device equipped with a 3 - 13 MHz multi-frequency linear transducer was used. The right femoral artery was identified with the transducer positioned transversely on the right triangle femoral area. Peak systolic velocity, end-diastolic velocity was measured. The Resistivity Index and Pulsatility Index were calculated automatically by the ultrasound machine software. Three measurements were obtained with the Doppler spectrum. The values of peak systolic velocity, end-diastolic velocity, Resistivity Index, Pulsatility Index and femoral artery diameter were expressed as Mean +/- Standard Deviation (SD). Discussion: No studies regarding to femoral artery Dopplerfluxometry in healthy dogs were found in the literature. These results can be used as normal reference values of Dopplerfluxometric parameters for adult dogs. The literature cited only Dopplerfluxometric values of renal arteries, abdominal aorta and of the internal thoracic artery. The normal values of arterial Dopplerfluxometry is necessary to identify the spectral quantitative characteristics of the blood flow for diagnosis and prognosis of vascular diseases. Authors referred to changes in blood perfusion by Dopplerfluxometry examination, but no changes in B-mode ultrasonography. The femoral Resistivity Index values can be used to correlate the postoperative evolution in dogs submitted to femoral bone, hip and knee surgeries, since Dopplerfluxometry allows blood flow assessment in the femoral region muscles. Changes in the heart rate, blood pressure, stress, exercise, and diseases as hypotension, renal lesion, hepatic diseases, diabetes, hyperadrenocorticism can change the Dopplerfluxometric parameters. All dogs which used in this study were clinically healthy, and were used beagle dogs due to lowest variations within breed. Sedation was avoid due to possible changes in Dopplerfluxometric parameters since the use of sedation or tranquilization in animals is strongly discussed due to possible hemodynamic changes that may occur during the examination. In conclusion, the mean values of the right femoral artery Dopplerfluxometry in male and female adult healthy dogs is Resistivity Index (0.887); Pulsatility Index (1.599); peak systolic velocity (124.41 cm/s), end-diastolic velocity (14.12 cm/s), femoral artery diameter (3.9 nun).
Keywords: resistivity index; pulsatility index; dopplerfluxometric parameters; small animals; hip dysplasia